KEMAMPUAN MAHASISWA PADA MATA KULIAH BAHASA DAN SASTRA INDONESIA - Ruspan Takasi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
A study has been conducted on the Profile of the Competence of Early Semester Students at UPBJJ Universitas Terbuka (UT) Kendari in the Indonesian Language and Literature Course for Elementary Schools. This research aims to assess the initial Indonesian language competence of all students at UPBJJ UT Kendari—a crucial skill that must be mastered by future educators—and to identify differences in student competence across various study groups (pokjar).The sample was selected using purposive sampling, where students were chosen from pokjars representing both urban and rural areas. Six pokjars were included as samples: Sikeli and Lainea representing rural areas, Kendari representing the provincial capital, and Unaaha and Wanggudu representing district capitals. The results showed that the average scores of students in the Indonesian Language and Literature course across all sample pokjars fell into the “very good” category. The lowest average score was from the Sikeli pokjar at 85.95, while the highest was from the Unaaha pokjar at 91.92. These findings indicate that the quality of instruction at UPBJJ UT Kendari, particularly in the Indonesian Language and Literature course, is relatively even across regions. An ANOVA test revealed that, at a confidence level of α = 0.05, the F-value obtained was Fcalculated = 28.74 > Ftable = 2.42, indicating that at least one pokjar had a significantly different average score compared to the others. A follow-up BNT (Least Significant Difference) test showed that students from the Sikeli, Kendari, and Wanggudu pokjars had significantly lower average scores compared to students from the Lainea and Unaaha pokjars. This suggests that students from rural areas do not necessarily perform worse than those from urban areas.